Reverse Semi‐Combustion Driven by Titanium Dioxide‐Ionic Liquid Hybrid Photocatalyst. Issue 20 (7th September 2020) - Qadir, Muhammad I.; Zanatta, Marcileia; Pinto, Jose; Vicente, Isabel; Gual, Aitor; Smith, Emily F.; Neto, Brenno A. D.; de Souza, Paulo E. N.; Khan, Sherdil; Dupont, Jairton; Alves Fernandes, Jesum
Abstract: Unprecedented metal‐free photocatalytic CO2 conversion to CO (up to 228±48 μmol g −1 h −1 ) was displayed by TiO2 @IL hybrid photocatalysts prepared by simple impregnation of commercially available P25‐titanium dioxide with imidazolium‐based ionic liquids (ILs). The high activity of TiO2 @IL hybrid photocatalysts was mainly associated to (i) TiO2 @IL red shift compared to the pure TiO2 absorption, and thus a modification of the TiO2 surface electronic structure; (ii) TiO2 with IL bearing imidazolate anions lowered the CO2 activation energy barrier. The reaction mechanism was postulated to occur via CO2 photoreduction to formate species by the imidazole/imidazole radical redox pair, yielding CO and water. Abstract : Hybrid theory : An effective method to prepare TiO2 @IL semiconductor‐liquid junctions for CO2 photo‐conversion is developed. The ionic liquid (IL) plays a dual role by inducing a shift of the valence band with simultaneously decreasing the band gap as well as continuous generation of formate radicals, which suggests a decrease of CO2 activation energy barrier and thus improves the catalyst performance (yield and selectivity to CO).